Dr. Karthik Ram — Deep Plane Facelift — Chennai - Ram, Karthik (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Karthik Ram, practicing in Chennai, India. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003131; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; india; chennai